Psychological Distress among Healthcare and Non-Healthcare Workers during the COVID-19 Pandemic: This Too Shall Pass - Shazma Khan, Fatima Zaina, Quratulain Khan, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: This study aimed to evaluate the psychological distress experienced by healthcare and non-healthcare professionals working in a hospital setting during the Coronavirus Disease 2019 (COVID-19) pandemic. Methodology: This survey-based cross-sectional study included 361 professionals (288 healthcare and 73 non-healthcare professionals) working at Ziauddin University Hospital, Karachi, Pakistan. Psychological distress was assessed using Depression Anxiety Stress Scale – 21 (DASS-21). Results: There was a higher prevalence of anxiety, depression, and stress among healthcare professionals as compared to the non-healthcare professionals, as indicated by the mean depression, anxiety, and stress scores on DASS-21 (p<0.05). The univariate logistic regression analysis showed that the odds of psychological distress were similar in both genders and individuals of all age groups. Healthcare professionals were twice more likely to be severely depressed and stressed as compared to non-healthcare professionals (p<0.05). Conclusion: This study concludes that psychological distress is more prevalent among healthcare workers than non-healthcare workers. Keywords: Psychological Distress, COVID-19, Anxiety, Depression, Stress, Healthcare Workers, Non-Healthcare Workers.